Segment Reversal in Kuliak and its Relationship to Nilo-Saharan (The University of Nairobi Journal of Language and Linguistics, 2026)
The paper discusses a pervasive feature of the Kuliak languages, a branch of Nilo-Saharan, consisting of two living languages, Ik and So, plus the moribund Nyang’i. Many CV syllables in cognate forms in other branches of Nilo-Saharan are realized as VC in Kuliak. This feature is not so constant as to constitute a morphological rule but applies to a significant number of lexemes in comparison with other Nilo-Saharan languages. The paper begins with an introduction to the literature on Kuliak languages and their status, then provides data tables from unpublished and published sources to support the existence of this process. The author's hypothesis is that this arises at the interface between morphology and phonology, and that it arises from the convergence of two processes: affix copying of common elements (-k- and -t-) and erosion from the front.
Keywords: Nilo-Saharan; Kuliak; morphology; historical linguistics; Uganda